Dynamics Analysis of the Main Indicators of the Higher Education System in the Regions of the Volga Federal District - Anatolevna Grigoreva, Ekaterina (2021)
The relevance of the chosen topic is due to the present rise of humanity to a new wave of scientific and technological progress, which is based on various achievements in high technologies of informatics, microelectronics, nanotechnology, genetic engineering, space exploration, etc. In these conditions, the education sector, which acts as a supplier of personnel, has become a priority direction of the state economic social policy of highly developed countries.